2011
DOI: 10.1539/joh.11-0156-fs
|View full text |Cite
|
Sign up to set email alerts
|

Association between Visual Message and Health Knowledge in a 4‐month Follow‐up Study at Worksites

Abstract: This study evaluated a simple workplace intervention that used visual messages to create awareness of two highly specific recommendations for good health. Methods: Four worksites were recruited in Iwakuni, Japan. The 4-month intervention used three promotional media-A2-size posters, A4-size flyers and displays on the company intranet. The visual messages were designed with silhouettes, pictograms and slogans. K n o w l e d g e a c q u i s i t i o n c o n c e r n i n g t h e t w o recommendations (daily vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For example, item “[3] Provide educational materials (posters, brochures, pamphlets, etc) on improving PA/HE” had a relatively high implementation rate and a high implementation intention rate, which was common to both PA and HE. Although providing educational materials improves knowledge, attitudes, and health status, 24 , 25 it is difficult for small and medium corporations that do not have occupational health professionals to select and provide educational materials, which vary in content and type, to their employees. Therefore, the implementation rate of this item can be further increased by proposing effective educational materials that match the specific health problems of the corporation and by providing methods that match the corporate environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, item “[3] Provide educational materials (posters, brochures, pamphlets, etc) on improving PA/HE” had a relatively high implementation rate and a high implementation intention rate, which was common to both PA and HE. Although providing educational materials improves knowledge, attitudes, and health status, 24 , 25 it is difficult for small and medium corporations that do not have occupational health professionals to select and provide educational materials, which vary in content and type, to their employees. Therefore, the implementation rate of this item can be further increased by proposing effective educational materials that match the specific health problems of the corporation and by providing methods that match the corporate environment.…”
Section: Discussionmentioning
confidence: 99%
“…This paper aims to select the most appropriate intentional stimulus as the communication channel to motivate and encourage energy conservation behaviour among government office users so that they can voluntarily change their conservation behaviour. Moreover, an intentional stimulus is suggested in this research because of its successful findings in previous research, including an application in a health education campaign (Sugiyama et al, 2011;Chang et al, 2011;White, Webster & Wakefield, 2008). Furthermore, it has been successful in promoting stair use through the intervention of visual messages in office buildings (Kwak et al, 2007;Eves, Webb & Mutirie, 2006) and shopping malls (Kerr, Eves & Carrol, 2001).…”
Section: Energy Stimulusmentioning
confidence: 95%
“…For example, medical professionals could effectively improve the health knowledge of people at high risk of stroke [ 44 ]. In addition, multiple studies indicated that health information could be disseminated by WeChat [ 45 , 46 ], internet/social media [ 47 , 48 ], visual messages [ 49 ], text books [ 50 ], blogs [ 51 ], social media [ 52 ], iPad-based app [ 53 ], short-video app TikTok [ 54 , 55 ], Sina Weibo [ 56 ], booklet [ 57 ], mass media [ 58 ], and web-based educational film [ 59 ]. Consistent with literature, we therefore hypothesized: Hypothesis 2: There existed ethnic disparities in access to health knowledge sources among the floating population in China.…”
Section: Literature Reviewmentioning
confidence: 99%